LMA gastro™ airway is feasible during upper gastrointestinal interventional endoscopic procedures in high risk patients: a single-center observational study - Schmutz, Axel; Loeffler, Thomas; Schmidt, Arthur; Göbel, Ulrich (BMC anesthesiology, 2020)
Nonoperating room anesthesia during gastroenterological procedures is a growing field in anesthetic practice. While the numbers of patients with severe comorbidities are rising constantly, gastrointestinal endoscopic interventions are moving closer to minimally invasive endoscopic surgery. The LMA Gastro™ is a new supraglottic airway device, developed specifically for upper gastrointestinal endoscopy and interventions. The aim of this study was to evaluate the feasibility of LMA Gastro™ in patients with ASA physical status ≥3 undergoing advanced endoscopic procedures.
Gesehen am 12.11.2024